Analisis Pengaruh Pengalaman Organisasi terhadap Produktivitas Tenaga Kerja Lulusan Fmipa Unisba Angkatan 2018 - Evania Putri; Indiriyani (UNISBA Press, 2024)
Abstract. Skilled labor with high productivity is one of the key drivers of the employment sector. This labor productivity can be supported by several factors, including organizational experience. The purpose of this research is to obtain information on whether organizational experience indeed influences labor productivity by using the Simple Regression Analysis method. The population used in this study consists of graduates from the Faculty of Mathematics and Natural Sciences at the Islamic University of Bandung, class of 2018. The analysis results show that organizational experience has been proven to affect labor productivity. This research can provide information and an overview of the application of Simple Regression Analysis in proving the influence on a certain factor, as well as offer insights for students to prepare for the workforce by participating in organizations. Abstrak. Tenaga kerja yang terampil dengan produktivitas tinggi adalah salah satu kunci penggerak sektor ketenagakerjaan. Produktivitas tenaga kerja ini dapat didukung dengan beberapa hal, diantaranya adalah pengalaman organisasi. Tujuan penelitian ini adalah memperoleh informasi apakah benar pengalaman organisasi berpengaruh terhadap produktivitas tenaga kerja dengan menggunakan metode Analisis Regresi Sederhana. Populasi yang digunakan adalah Lulusan FMIPA Universitas Islam Bandung angkatan 2018. Dari hasil analisis, diperoleh bahwa pengalaman organisasi terbukti berpengaruh terhadap produktivitas tenaga kerja. Dari penelitian ini bisa menjadi informasi dan gambaran terkait penerapan metode Analisis Regresi Sederhana dalam pembuktian pengaruh terhadap suatu hal, dan menjadi gambaran bagi mahasiswa agar mempersiapkan dunia kerja dengan mengikuti organisasi.